Protein Crystallization As a Process Step in a Novel Meso Oscillatory Flow Reactor: Study of Lysozyme Phase Behavior - Filipa Castro (2016)
In the present work, it is reported for the first time the study of the applicability of a novel meso oscillatory flow reactor (meso-OFR) for protein crystallization as a process step. Crystallization assays carried out in the designed device enabled to derive a two-dimensional lysozyme phase diagram (lysozyme concentration against sodium chloride concentration). Results evidence the formation of several types of crystals (different size and shape), with a strong influence of salt concentration on crystal shape. Results also show that lysozyme remains active at the end of the experiments. Furthermore, it was possible to verify the reduction of the metastability zone when compared to lysozyme crystallization conducted under quiescent conditions. Induction times were also measured by online monitoring of the turbidity of the crystallization solution, obtained values being between 41 and 900 min. Beyond providing improved understanding of protein phase behavior under oscillatory flow mixing, the results are very promising regarding the feasibility of the designed methodology for protein crystallization as a process step.